REDUKSIONISME EKSPLANATIF UNTUK ANTROPOLOGI TRANSENDENTAL JAWĀDĪ ĀMULĪ - Cipta Bakti Gama (Sekolah Tinggi Agama Islam Sadra, 2015)
This article explains how an explanatory reductionism theory can be applied to the integration of various disciplines in Jawādī Āmulī’s transcendent anthropology. The author explores some extent of possibility and certain forms of application of explanatory reductionism for such transcendent anthropology. The author uses Ricoeurian hermeneutics method to emphasize distantiation, interpretation, and appropriation. It concludes that, first, Jawādī Āmulī attempts to implement certain forms of an explanatory reductionism in integrating philosophy, ‘irfān, and Quranic exegesis. Second, reductionism can be applied in the integration of various disciplines of knowledge for constructing transcendent anthropology which is approached through the objective effects of human existence in the material universe.